Solar USB charger / Alif Fatihi Abdul Fatah & Muhammad Ashraff Abdul Raffar - Abdul Fatah, Alif Fatihi; Abdul Raffar, Muhammad Ashraff (2015)
As world's resources are diminishing, government and non-government are pushing a greener solution through the use of renewable energy sources. Some scientists said that solar energy will be future energy source. The portable solar phone charger is one of the devices that use light to charge a phone. It is really portable people on the road or n a camping can carry it into their pocket charge their phone where ever they want. A solar charger can charge a phone anywhere but it should be considered if it is as efficient as normal power bank. This project show that the world is now a bit closer to the perfection of solar technology. Further studies on solar technology would help for the study on renewable energy.